2021
DOI: 10.1136/rapm-2021-103092
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the use of buprenorphine for opioid use disorder in the perioperative setting

Abstract: approved the creation of a Multisociety Working Group on Opioid Use Disorder (OUD), representing the fields of pain medicine, addiction and pharmacy health sciences. An extensive literature search was performed, and a modified Delphi process was used to assess the literature and expert opinion for each topic, with 100% consensus being achieved on the statements and each recommendation. The consensus statements were then graded by the committee members using the US Preventive Services Task Force grading of evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…A patient-centered approach investing in shared decision-making and expectations is essential to all MOUD strategies when managing acute surgical pain. Prevailing consensus-based recommendations 2 advise continuation of methadone and buprenorphine MOUD without interruption throughout the perioperative period. Secondary to its µ-opioid receptor antagonism, naltrexone dosed for OUD treatment (in contrast to low-dose naltrexone for treating chronic pain) may need to be discontinued before surgery if acute opioid dosing is anticipated.…”
Section: Perioperative Considerations For Patients Prescribed Moudmentioning
confidence: 99%
See 1 more Smart Citation
“…A patient-centered approach investing in shared decision-making and expectations is essential to all MOUD strategies when managing acute surgical pain. Prevailing consensus-based recommendations 2 advise continuation of methadone and buprenorphine MOUD without interruption throughout the perioperative period. Secondary to its µ-opioid receptor antagonism, naltrexone dosed for OUD treatment (in contrast to low-dose naltrexone for treating chronic pain) may need to be discontinued before surgery if acute opioid dosing is anticipated.…”
Section: Perioperative Considerations For Patients Prescribed Moudmentioning
confidence: 99%
“…Prospective studies on the optimal perioperative buprenorphine dosing are lacking and informed primarily by case reports and consensus-based protocols. Kohan et al 2 in 2021 released multisociety expert recommendations regarding buprenorphine in the perioperative period. Although there is debate about opioid receptor availability with higher doses of buprenorphine, home dose buprenorphine is recommended to be continued before surgery, as tapering or discontinuing buprenorphine before surgery may increase the risk of a setback and possible death.…”
Section: Perioperative Considerations For Patients Prescribed Moudmentioning
confidence: 99%
“…7,8 A recent multidisciplinary workgroup suggested that there was a moderate level of evidence that patients on buprenorphine should be continued at their home dose during the preoperative period and that multimodal analgesia including short-acting full agonist opioids could be used during the postoperative phase. 9 Within the pregnant population, Meyer et al compared postpartum pain control and opioid utilization following vaginal and cesarean deliveries and found no differences in intrapartum pain or analgesic utilization between patients prescribed buprenorphine and their matched controls that were not on medications for OUD (MOUD). 10 However, those undergoing cesarean section deliveries (19 women) experienced more postpartum pain and required 47% more opioid analgesics than their matched controls.…”
Section: Substance Abuse: Research and Treatmentmentioning
confidence: 99%
“… 7 , 8 A recent multidisciplinary workgroup suggested that there was a moderate level of evidence that patients on buprenorphine should be continued at their home dose during the preoperative period and that multimodal analgesia including short-acting full agonist opioids could be used during the postoperative phase. 9 …”
Section: Introductionmentioning
confidence: 99%
“…For those surgeries where severe pain is anticipated, either dose increases or adjustments in the frequency interval should be considered. For those patients who present for surgery untreated, current recommendations encourage initiating buprenorphine preoperatively [14 ▪▪ ,15].…”
Section: Relevance Of Abuse In the Perioperative Periodmentioning
confidence: 99%